Effects of norepinephrine transporter gene variants on NET binding in ADHD and healthy controls investigated by PET. Issue 3 (17th December 2015) - Sigurdardottir, Helen L.; Kranz, Georg S.; Rami‐Mark, Christina; James, Gregory M.; Vanicek, Thomas; Gryglewski, Gregor; Kautzky, Alexander; Hienert, Marius; Traub‐Weidinger, Tatjana; Mitterhauser, Markus; Wadsak, Wolfgang; Hacker, Marcus; et al.
Abstract: Attention deficit hyperactivity disorder (ADHD) is a heterogeneous disorder with a strong genetic component. The norepinephrine transporter (NET) is a key target for ADHD treatment and the NET gene has been of high interest as a possible modulator of ADHD pathophysiology. Therefore, we conducted an imaging genetics study to examine possible effects of single nucleotide polymorphisms (SNPs) within the NET gene on NET nondisplaceable binding potential (BPND ) in patients with ADHD and healthy controls (HCs). Twenty adult patients with ADHD and 20 HCs underwent ( S, S ) ‐ [ 18 F]FMeNER‐D2 positron emission tomography (PET) and were genotyped on a MassARRAY MALDI‐TOF platform using the Sequenom iPLEX assay. Linear mixed models analyses revealed a genotype‐dependent difference in NET BPND between groups in the thalamus and cerebellum. In the thalamus, a functional promoter SNP (−3081 A/T) and a 5′‐untranslated region (5′UTR) SNP (−182 T/C), showed higher binding in ADHD patients compared to HCs depending on the major allele. Furthermore, we detected an effect of genotype in HCs, with major allele carriers having lower binding. In contrast, for two 3′UTR SNPs (*269 T/C, *417 A/T), ADHD subjects had lower binding in the cerebellum compared to HCs depending on the major allele. Additionally, symptoms of hyperactivity and impulsivity correlated with NET BPND in the cerebellum depending on genotype. Symptoms correlated positively with cerebellar NET BPND for the major allele, while symptoms correlated negatively to NET BPND in minor allele carriers. Our findings support the role of genetic influence of the NE system on NET binding to be pertubated in ADHD. Hum Brain Mapp 37:884–895, 2016 . © 2015 The Authors Human Brain Mapping Published by Wiley Periodicals, Inc .